2022
DOI: 10.7717/peerj.14385
|View full text |Cite
|
Sign up to set email alerts
|

Could hand-eye laterality profiles affect sport performance? A systematic review

Abstract: Background Laterality effects on sports performance have been a field of interest for the sports sciences, especially in asymmetrical sports, which require the preferential use of one side of the body. Some sports in particular involve the visual system and ocular laterality, due to the need to clearly focus on a dynamic object (ball, opponent, projectile, etc.). The relationship between manual and ocular laterality results in two perceptual-motor profiles, one where the dominant hand and eye are ipsilateral (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
(91 reference statements)
0
6
0
Order By: Relevance
“…For eyedness, about 30% of people in our sample (about the same proportions for female and male participants) had a left-eye preference, which is consistent with what is reported in the literature [ 10 ]. The weak link between eyedness and gripping an ice-hockey stick is not surprising considering that in bilateral asymmetric sports like cricket and golf, the advantage of a cross-lateral stance is not modulated by eyedness [ 14 , 15 ] In the review by Moreno et al [ 28 ], cross hand-eye lateral preference would be helpful in tennis and some team sports, and hockey is mentioned in these “team sports”. However, it is not specified if it is ice-hockey or field hockey, and what belongs specifically to hockey; we have not found this information in the original paper [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For eyedness, about 30% of people in our sample (about the same proportions for female and male participants) had a left-eye preference, which is consistent with what is reported in the literature [ 10 ]. The weak link between eyedness and gripping an ice-hockey stick is not surprising considering that in bilateral asymmetric sports like cricket and golf, the advantage of a cross-lateral stance is not modulated by eyedness [ 14 , 15 ] In the review by Moreno et al [ 28 ], cross hand-eye lateral preference would be helpful in tennis and some team sports, and hockey is mentioned in these “team sports”. However, it is not specified if it is ice-hockey or field hockey, and what belongs specifically to hockey; we have not found this information in the original paper [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The way handedness, eyedness, and footedness was tested is also a limitation. For example, there are different ways of assessing eye preference or dominance [ 28 ], including using photo and a pointing task [ 15 ], instead of using preferences for a one-eyed activity. As for the bilateral tasks, it is not excluded that the order of questions may have had an impact, with the response to one question having repercussion on the way of representing the placement of hands on the subsequent question.…”
Section: Discussionmentioning
confidence: 99%
“…For example, an ipsilateral arrangement for hand and eye dominance appears to convey an advantage in different throwing and aiming behaviours [6,[19][20][21], so that novice archers with ipsilateral hand-eye patterns have an advantage compared to archers who are cross-lateralized for hand and eye [22]. Conversely, a cross-lateralized hand-eye profile may enhance perceptual-motor performance in other ways, providing an advantage in sports such as tennis, golf, football, and other team sports (see [23] for a review). It has been suggested that being cross-lateralized may be particularly advantageous in duels when an individual is left-handed and right-eyedominant [24].…”
Section: Introductionmentioning
confidence: 99%
“…Dominance refers to the preference most humans show for one side of their body over the other to do activities like writing, eating or sports especially in asymmetrical sports, which require the preferential use of one side of the body. 1,2 Whereas functional dominance happens in the paired organs of the body, such as hands, legs, eyes, ears and cerebral hemispheres; the exact mechanisms resulting in dominance as well as the strength and quality of lateralisation remain unclear. 2,3,4 Eye dominance is the superiority or preference of one eye over the other for visual, sensory and oculomotor tasks in individuals with similar vision and other extraocular structures.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Whereas functional dominance happens in the paired organs of the body, such as hands, legs, eyes, ears and cerebral hemispheres; the exact mechanisms resulting in dominance as well as the strength and quality of lateralisation remain unclear. 2,3,4 Eye dominance is the superiority or preference of one eye over the other for visual, sensory and oculomotor tasks in individuals with similar vision and other extraocular structures. Conversely, on those with pathological features or ocular defects such as the presence of anisometropia, paralysis of extraocular muscles, unilateral cataract or other aspects that would tend to determine which eye with manifest suppression and therefore be the non-dominant eye, the preference could be easily understood.…”
Section: Introductionmentioning
confidence: 99%